PENGELOLAAN DAN PEMANFAATAN DANA DESA UNTUK PEMBERDAYAAN MASYARAKAT (Studi Kasus Di Gampong Gunong Meulinteung Kecamatan Panga Kabupaten Aceh Jaya) - Aminah Aminah; Novita Sari (Universitas Teuku Umar, 2018)
This research aims to explain about management and utilization of village funds in the community empowerment program in Gampong Gunong Meulinteung Panga Sub-district of Aceh Jaya. The data that is required in writing is obtained through library research and field. Library research done with how to read text books, legislation, and other reading material related to this research. While field research done by interviewing informants. The results of the study showed that the community empowerment program in Gampong Gunong Meulinteung Panga Sub-district of Aceh Jaya yet optimal. This is because there are still many obstacles that dhadapi by the apparatus of Gampong in running the program. community empowerment program that has been done by the Gampong Gunong Meulinteung namely (1) Simpan Pinjam Perempuan (SPP), (2) empowerment of the field of the Palm Oil Plantation (3) The Empowerment in the field of Agriculture (4) Sewing Empowerment Sewing (5) Empowerment of farming field. Of the five programs that run only three programs that sustainable development is the empowerment of the field of the Palm Oil Plantation, Empowerment in the field of agriculture and Empowerment of farming FieldKeywords: Community Empowerment, Utilization and Village Funds.